Using whole rock and in situ pyrite chemistry to evaluate authigenic and hydrothermal controls on trace element variability in a Zn mineralized Proterozoic subbasin. (1st February 2022) - Magnall, Joseph M.; Gleeson, Sarah A.; Hayward, Nicholas; Oelze, Marcus
Abstract: The mid-Proterozoic stratigraphy of the McArthur Basin (Australia) contains some of the most well-preserved sedimentary rocks of Precambrian age, which are also host to giant, clastic dominant (CD-type) massive sulfide Zn deposits. The most recently discovered CD-type deposit (the Teena deposit) is located in the Teena subbasin and hosted by the 1.64 Ga Barney Creek Formation. The Teena subbasin, therefore, provides the perfect natural laboratory for evaluating authigenic and hydrothermal controls on trace element (TE) variability, both of which contribute to paleoenvironmental reconstructions and ore deposit models. As the Teena deposit formed beneath the paleoseafloor, this also provides the opportunity to evaluate TE zonation around a fossilized subseafloor replacement hydrothermal system. In situ laser ablation inductively coupled mass spectrometry (LA-ICP-MS) has been used to define compositional end members in diagenetic and hydrothermal pyrite. The overgrowth of hydrothermal sulfides on diagenetic pyrite is associated with TE anomalism (Tl, Pb, As, Zn) that extends > 100 meters above the main high grade sulfide mineralization the Teena subbasin. The vertical zonation in TEs is consistent with the infiltration of hydrothermal fluids into overlying hangingwall sediments that were undergoing diagenesis. Bulk rock lithogeochemical data record covariation between total organic carbon (TOC) and a suite of TEs (Mo, Co, Ni, V). We suggest this was caused by local hydrographic factors during deposition of the Barney Creek Formation. High TOC/P molar ratios, resulting from regeneration of P in a euxinic water column, are associated with an interval overlying the main maximum flooding surface in the subbasin. The relationships between TOC, P and TEs resemble the redox architecture of a silled basin rather than an open marine margin. Sulfidic conditions developed during periods of high productivity, which were linked to nutrient supply that was enhanced by connectivity with surrounding water masses. The evidence of redox bistability, involving a delicate balance between ferruginous (anoxic, non-sulfidic) and euxinic (sulfidic) conditions, is consistent with recent models for other mid-Proterozoic sedimentary units. Nevertheless, there was a strong localised (10 1 km 2 ) control on the authigenic and hydrothermal TE chemistry of the Barney Creek Formation in the Teena subbasin, which highlights a key challenge when extrapolating from data collected in partially restricted intracontinental marine settings.